Common beans in Africa and their constraints - Allen, David J.; Dessert, M.; Trutmann, P.; Voss, J. (International Center for Tropical Agriculture, 1989)
Beans are grown in Africa in a wide range of environments, mainly in the cool highlands of central and tropical eastern Africa, leading to a diversity of cropping systems and agronomic constraints to production. Beans are cultivated for large-scale production or home consumption either in monoculture or in association. The main constraints to production are poor agronomic practices, soil infertility, lack of improved cv., water stress, weed competition, and diseases and pests. Main diseases affecting bean crops in Africa include viral diseases (BCMV, SBMV, BGMV, and BYMV), bacterial diseases (bacterial wilt and bacterial brown spot), and fungal diseases (angular leaf spot, anthracnose, rust, Ascochyta blight, and floury leaf spot). Suggestions for disease management are given, highlighting the use of integrated control. Estimates of annual production per region and crop losses due to pathogens are given in table form. (CIAT)